The impact of the emergence of delivery companies on increasing consumption among individuals - Mouffouk, Houssem; Korichi, Salah; Taibi, Abdelatif; Redjem, Khaled (The International tax journal, 2025)
This study investigates the impact of the emergence of delivery companies on the online purchasing behavior of individuals, focusing specifically on consumers in Ouargla, Algeria. Employing a descriptive analytical approach, data were collected using a structured questionnaire distributed to 45 respondents. Statistical analyses were performed using SPSS27 software. The findings revealed that the emergence of delivery companies significantly increased individuals' online consumption behavior. Among the examined characteristics of delivery services (professionalism, cost, and comfort) professionalism and comfort showed statistically significant impacts on consumer purchasing behavior, while cost did not demonstrate a significant effect. These results suggest that consumers prioritize convenience and reliability offered by delivery services over cost considerations. The study contributes valuable insights into consumer behavior dynamics within the context of emerging markets, highlighting the critical role of service quality and convenience in shaping online purchasing decisions.